THE ORGANOMETRIC PARAMETERS OF WHITE RATS’ SPLEEN AFTER INJECTIONS OF CYCLOPHOSPHANUM AND IMUNOFANUM - Kashchenko, S.A.; Zolotarevskaya, M.V. (World of Medicine and Biology, 2010)
The organomethric changes of the structure of the white rats males spleen of the different ages have been investigated after injections of the cyclophosphanum one time and imunofanum from scheme. Finding changes of the morphological parameters from control show on the high reactivity of the spleen under influence immune drugs.
Keywords: rats; spleen; organomethric; cyclophosphanum; imunofanum